2018
DOI: 10.1093/ofid/ofy209.143
|View full text |Cite
|
Sign up to set email alerts
|

1758. Impact of Accelerate Pheno™ Rapid Blood Culture Detection System on Laboratory and Clinical Outcomes in Bacteremic Patients

Abstract: BackgroundMolecular-based automated systems for the rapid diagnosis of bacterial infections have potential to improve patient care. The Accelerate Pheno™ blood culture detection system (ACCEL) is an FDA approved platform that allows for identification (ID) and antimicrobial susceptibility testing (AST) 8 hours following growth in routine culture.MethodsThis is a single-center retrospective chart review of bacteremic adult inpatients before and after implementation of ACCEL. Laboratory and clinical data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…We observed that providers were more willing to de-escalate empirical antimicrobial therapy after final AST (provided by AXDX) as opposed to after ID and resistance gene results alone, primarily due to the possibility of undetected resistance with genotypic testing. This is similar to that for other institutions that have shown time from Gram stain to ID and AST, time to optimal therapy, time to step-down antimicrobial therapy, and length of stay outcomes through AXDX utilization ( 14 , 15 ). This earlier de-escalation of antimicrobial therapy in Enterobacteriaceae bloodstream infections can significantly help decrease Clostridioides difficile infection rates, as recently reported in literature ( 16 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We observed that providers were more willing to de-escalate empirical antimicrobial therapy after final AST (provided by AXDX) as opposed to after ID and resistance gene results alone, primarily due to the possibility of undetected resistance with genotypic testing. This is similar to that for other institutions that have shown time from Gram stain to ID and AST, time to optimal therapy, time to step-down antimicrobial therapy, and length of stay outcomes through AXDX utilization ( 14 , 15 ). This earlier de-escalation of antimicrobial therapy in Enterobacteriaceae bloodstream infections can significantly help decrease Clostridioides difficile infection rates, as recently reported in literature ( 16 ).…”
Section: Discussionsupporting
confidence: 82%
“…This is similar to other institutions that have shown time from gram stain to ID and AST, time to optimal therapy, time to step-down antimicrobial therapy, and length of stay outcomes through AXDX utilization. [17][18] This earlier de-escalation of antimicrobial therapy in Enterobacteriaceae bloodstream infections can significantly help decrease Clostridioides difficile infection rates as recently reported in literature. 19 on October 29, 2020 by guest http://aac.asm.org/…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, usage of certain antibiotics such as cefepime, aminoglycosides, piperacillin/tazobactam, and vancomycin could have decreased with use of Accelerate Pheno™. In a single-center before-and-after cohort study of actual clinical use, implementation of Accelerate Pheno™ was associated with shorter time to optimal therapy, length of stay, and antibiotic duration of therapy as compared with historical conventional identification (including MALDI/TOF) and antimicrobial susceptibility testing methods [17].…”
Section: Impact Of Rdt On Amsmentioning
confidence: 96%